Asked by shaveta.rishabh | 9th Jul, 2019, 11:35: PM
f(y) = y3 - 7y + 6
The constant term in f(y) is 6.
Factors of 6 = ± 1, ±2, ±3, ±6
f(-1) = (-1)3 - 7(-1) + 6 = -1 + 7 + 6 = 12≠ 0
f(1) = 0
Therefore by Factor theorem,
(y - 1) is a factor of f(y).
Divide f(y) by (y - 1) by using long division method.
→ y3 - 7y + 6 = (y - 1)(y2 + y - 6) = (y - 1)(y + 3)(y - 2)
Answered by Yasmeen Khan | 10th Jul, 2019, 10:28: AM
- (×-1)is afactor of (2×^4+9×^3+6×^3-11×-6
- Find the value of ′a′, if (x− a) is a factor of x^3 − ax^2 + x + 2.
- If x-2 and x-1/2 both are the factor of the polynomials nx^2 - 5x +m , then show that m=n .
- Find what must be subtracted from 4y4+12y3+6y2+50y+26 so that obtained polynomial is exactly divisible by y2+4y+2
- Factorise : 2u3-3u2-17u+30
- Using factor theorem factorise the polynomial x rays to 4 + x rays to 3 -7x rays to 2 -x +6
- Find integral zeros of 2xcube +3xsquare -8x-12
- Factorise: 36q²+54q+20
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number